Efficient Secure-Channel Free Public Key Encryption with Keyword Search for EMRs in Cloud Storage. - Guo, Lifeng; Yau, Wei-Chuen (Journal of Medical Systems, 2015)
Searchable encryption is an important cryptographic primitive that enables privacy-preserving keyword search on encrypted electronic medical records (EMRs) in cloud storage. Efficiency of such searchable encryption in a medical cloud storage system is very crucial as it involves client platforms such as smartphones or tablets that only have constrained computing power and resources. In this paper, we propose an efficient secure-channel free public key encryption with keyword search (SCF-PEKS) scheme that is proven secure in the standard model. We show that our SCF-PEKS scheme is not only secure against chosen keyword and ciphertext attacks (IND-SCF-CKCA), but also secure against keyword guessing attacks (IND-KGA). Furthermore, our proposed scheme is more efficient than other recent SCF-PEKS schemes in the literature.